Applying resilience thinking to ’ordinary’ cities: A theoretical inquiry - Dessie, Elizabeth (Bulletin of Geography. Socio-economic Series, 2018)
This paper assesses the prospective contribution of social-ecological resilience thinking in ad-vancing a theory of ’ordinary’ cities. Building on the hierarchical divide that continues to pre-scribe analyses and representations of cities in urban studies, the paper suggests that, while ideologically contentious, the conceptual configuration of resilience thinking, promoted essen-tially through notions of uncertainty, diversity and transformation, shows considerable poten-tial for interdisciplinary research. While remaining cautious about its analytical thresholds, applying the framework as it emerges from its ecological niche suggests that resilience think-ing can, alongside other concepts, play a part in creating an enabling environment for broaden-ing the way communities, neighbourhoods and institutions that form and connect cities across the globe are understood, studied and represented in urban theory; allowing us to recognise all cities and their citizens as relatable and ’ordinary’.